2018
DOI: 10.1016/j.nmni.2017.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Insertional inactivation of oprD in carbapenem-resistant Pseudomonas aeruginosa strains isolated from burn patients in Tehran, Iran

Abstract: In this study, we report the insertion sequence ISPpu21 in the oprD porin gene of carbapenem-resistant Pseudomonas aeruginosa isolates from burn patients in Tehran, Iran. Antibiotic susceptibility tests for P. aeruginosa isolates were determined. Production of metallo-β-lactamases (MBLs) and carbapenemase was evaluated and the β-lactamase-encoding and aminoglycoside-modifying enzyme genes were investigated by PCR and sequencing methods. The mRNA transcription level of oprD and mex efflux pump genes were evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 25 publications
1
45
0
Order By: Relevance
“…Although, PCR screening of clinically important carbapenemases indicated diverse distribution of several carbapenemases, bla NDM and bla OXA, particularly, bla OXA‐23 ‐like gene was found to be prevalent. Furthermore, most of the earlier studies have demonstrated efflux pump ( mexB and adeB ) overexpression and porin (OPrD, CarO and 33‐36 KD porin) loss to be secondary mechanisms of carbapenem resistance development among P. aeruginosa and A. baumannii (Poirel and Nordmann ; Shariati et al ; Chen et al ; Novović et al ). While, Shariati et al (), earlier reported 1·1–3·68 fold overexpression of mexB and approximately twofold reduced expression of OprD among carbapenem‐resistant P. aeruginosa, this study demonstrated approximately 16‐fold overexpression of mexB and complete loss of OprD among most of the CRPsA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although, PCR screening of clinically important carbapenemases indicated diverse distribution of several carbapenemases, bla NDM and bla OXA, particularly, bla OXA‐23 ‐like gene was found to be prevalent. Furthermore, most of the earlier studies have demonstrated efflux pump ( mexB and adeB ) overexpression and porin (OPrD, CarO and 33‐36 KD porin) loss to be secondary mechanisms of carbapenem resistance development among P. aeruginosa and A. baumannii (Poirel and Nordmann ; Shariati et al ; Chen et al ; Novović et al ). While, Shariati et al (), earlier reported 1·1–3·68 fold overexpression of mexB and approximately twofold reduced expression of OprD among carbapenem‐resistant P. aeruginosa, this study demonstrated approximately 16‐fold overexpression of mexB and complete loss of OprD among most of the CRPsA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, most of the earlier studies have demonstrated efflux pump ( mexB and adeB ) overexpression and porin (OPrD, CarO and 33‐36 KD porin) loss to be secondary mechanisms of carbapenem resistance development among P. aeruginosa and A. baumannii (Poirel and Nordmann ; Shariati et al ; Chen et al ; Novović et al ). While, Shariati et al (), earlier reported 1·1–3·68 fold overexpression of mexB and approximately twofold reduced expression of OprD among carbapenem‐resistant P. aeruginosa, this study demonstrated approximately 16‐fold overexpression of mexB and complete loss of OprD among most of the CRPsA. Similarly, the present study exhibited approximately 17·5‐fold overexpression of adeB among CRAB which was consistent with that of earlier findings of approximately 12·3‐fold adeB overexpression demonstrated by Chen et al ().…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…People infected with high doses of bacteria, or those exhibiting different immune responses, including female sex, are more likely to suffer from IBS after being infected with salmonella (McKendrick & Read, 1994;Mearin et al, 2005). 10 | P. AERUGINOSA AND IBS P. aeruginosa is a Gram-negative aerobic bacillus with a high antibiotic resistance that induces a variety of important infections such as cystic fibrosis and burn infections (Oliver, Cantón, Campo, Baquero, & Blázquez, 2000;Shariati, Azimi et al, 2018). Results of a recent study revealed a higher prevalence and level of the Pseudomonas genus in fecal and small intestinal samples from IBS patients than control subjects and considered P. aeruginosa as the predominant isolated species (Kerckhoffs et al, 2011).…”
Section: Salmonella and Ibsmentioning
confidence: 99%
“…84,85 Different studies in recent years have shown that Gram-positive and Gram-negative bacteria, such as vancomycin-resistant enterococci, methicillinresistant S. aureus (MRSA), Enterobacteriaceae with extended-spectrum b-lactamase and XDR A. baumannii and P. aeruginosa have caused the highest mortality among infected patients. 86,87 On the other hand, it should be noted that of extensively drug-resistant tuberculosis (XDR-TB), MDR Clostridium difficile and newly identified transmissible carbapenamase, New Delhi metallo-betalactamases (NDM) in Enterobacteriaceae are expanding all over the world, especially in developing countries, and may become a big problem in the coming years. 3,88,89 Intrinsic properties, such as external barriers, which prevent the entry of drugs into bacteria, natural mutations in antibiotic targets and acquired features, such as sequestration of the drug, efflux pumps and enzyme-dependent drug alterations cause such high levels of resistance to existing antibiotics.…”
Section: Global Concern For Mdr Xdr and Pdr Pathogensmentioning
confidence: 99%